Original paperPatient characteristics of children with cow’s milk allergy presenting with an allergy to extensively hydrolyzed whey and/or casein formulae used as part of an elimination diet - Nowacki, Zygmunt (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction : In the recent years the number of children with cow’s milk protein allergy (CMPA) presenting with allergies to extensively hydrolyzed whey (eHF-W) and casein formulae (eHF-C) respectively has increased. Aim: To present the patient characteristics of children with CMPA who presented with allergic reactions to eHF-W and/or eHF-C used as part of an elimination diet. Material and methods : A retrospective study was carried out for a group of 65 selected from of 359 children (3 to 12 months) affected with CMPA and allergy to eHF. Results: 18.1% (65/359) and 7.8% (28/359) from the group presented with allergic reactions to eHF-W and eHF-C, respectively. An allergic reaction to eHF-C occurred in 43% of the patients from the group (28/65). IgE-mediated CMPA presented with one of the following clinical manifestations: atopic dermatitis (AD) 94%, gastrointestinal symptoms (GI) 47%, respiratory symptoms (RS) 44%, anaphylactic reactions (AR) 26%. Non-IgE-mediated CMPA, on the other hand, manifested with: AD 97%, GI 22%, RS 10% .The observations showed that all 31 from the non-IgE mediated CMPA group with GI and AD manifestations presented with symptoms of eHF-C allergy (p = 0.001). In the IgE-mediated CMPA (n = 34) the following factors were statistically significant with relation to eHF-C allergy: CMPA manifesting with GI (p = 0.014) and AD. The occurrence of AR in response to cow’s milk protein (CMP) decreased the probability of an eHF-C allergy (p = 0.028) in a statistically significant way. Conclusions: Children with CMPA who presented with allergies to eHF-W and eHF-C had a higher frequency of clinical manifestation with GI and AD.